Poverty, Inequality, and Social Security During the COVID‐19 Pandemic: Evidence From Linked Swiss Tax Data - Oliver Hümbelin; Maurizio Strazzeri; Olivier Lehmann (Poverty & Public Policy, 2026)
ABSTRACT This paper examines the impact of the COVID‐19 pandemic on income and wealth inequality in Switzerland, with a particular focus on poverty dynamics and the role of the social security system. Using newly linked administrative tax data for four large cantons covering over a third of the Swiss population, we track changes in household income and liquid assets from 2019 to 2022. We find that the average net household income increased during the pandemic. Yet, income declines were concentrated among households at both the bottom and the top of the income distribution. Nevertheless, relative and absolute poverty rates remained stable. The observed developments are consistent with the interpretation that existing and newly introduced social security measures contributed toward stabilizing household finances during the pandemic. The findings are consistent with the view that timely state interventions may help cushion the social consequences of large‐scale economic shocks. However, the trajectory analysis reveals considerable heterogeneity in households' economic experiences, with income and asset losses being particularly pronounced among lower‐income households. The findings therefore suggest that aggregate poverty and inequality indicators may mask substantial economic vulnerability during periods of major economic disruption.